2008
DOI: 10.1113/jphysiol.2007.142158
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular challenge of exercising in the heat

Abstract: Exercise in the heat can pose a severe challenge to human cardiovascular control, and thus the provision of oxygen to exercising muscles and vital organs, because of enhanced thermoregulatory demand for skin blood flow coupled with dehydration and hyperthermia. Cardiovascular strain, typified by reductions in cardiac output, skin and locomotor muscle blood flow and systemic and muscle oxygen delivery accompanies marked dehydration and hyperthermia during prolonged and intense exercise characteristic of many su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
250
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(268 citation statements)
references
References 46 publications
7
250
0
11
Order By: Relevance
“…Sauna bathing leads to skin sweating-induced body fluid loss, which is a physiological response to hot temperature. 24 Tken together, these experimental findings suggest a biological plausibility to the inverse association between sauna and risk of hypertension. Our findings also suggest that the protective effect of sauna bathing on CVD may be via the blood pressure lowering effects of regular sauna bathing.…”
Section: Discussionmentioning
confidence: 94%
“…Sauna bathing leads to skin sweating-induced body fluid loss, which is a physiological response to hot temperature. 24 Tken together, these experimental findings suggest a biological plausibility to the inverse association between sauna and risk of hypertension. Our findings also suggest that the protective effect of sauna bathing on CVD may be via the blood pressure lowering effects of regular sauna bathing.…”
Section: Discussionmentioning
confidence: 94%
“…Heat exposure, strenuous exercise and dehydration pose a significant challenge to the cardiovascular system, and the transport of oxygen to exercising muscles and vital organs, such as the kidney (16). It has also been shown that muscles under these conditions release myoglobin that can produce acute kidney damage, especially in combination with dehydration (17)(18)(19).…”
Section: Wegman Et Almentioning
confidence: 99%
“…Foi observado que a água de coco teve o mesmo impacto que a água em relação a hidratação e o cardiovascular drift. Além disso, foi demonstrado que o cardiovascular drift pode afetar a prescrição do exercício pela FC em frequentadores de academia, devido à desidratação 17,18 . Sabe-se que não compensar a perda de líquidos, principalmente no exercício físico em ambientes quente e úmido, pode trazer sérias consequências à saúde e ao desempenho 19 .…”
Section: Discussionunclassified
“…A mensuração da FC, para determinação da "zona alvo de treinamento" é, talvez, a forma mais divulgada e utilizada para determinação da intensidade do exercício aeróbico em uma prescrição de exercício, sendo importante para obtenção dos objetivos de um programa de exercícios físicos 15 . Durante o cardiovascular drift, participantes de exercício físico aeróbico, podem reduzir o ritmo de trabalho físico, a fim de manter constante a FC dentro da zona alvo de treinamento pré-estabelecido, podendo resultar em esforço físico abaixo do pretendido em termos de intensidade 18 . O aumento da produção de calor, juntamente com a dificuldade de dissipar, pode promover aumentos na temperatura interna corporal pelos seus efeitos sobre o sistema nervoso central, que limita a capacidade de continuar o exercício 40 .…”
Section: Discussionunclassified
See 1 more Smart Citation